POST-CONFLICT TOURISM DEVELOPMENT IN INCLUSIVE TERMS: SMART CITY MODELS AND CLUSTERING OPPORTUNITIES IN KARABAKH - Namiq Nigar Namiq (European Research Materials, 2026)
The article analyzes the opportunities for inclusive tourism development in post-conflict areas, focusing on the Karabakh and East Zangezur economic regions. The region’s cultural-historical, natural, and economic potential creates favorable conditions for the development of tourism in various directions. The study examines the application of cluster approaches and “smart city” models, as well as the integration of digital governance mechanisms into the tourism sector, as key development directions. At the same time, international experience and state-led reconstruction policies are assessed as important factors in realizing the region’s tourism potential